2013
DOI: 10.1080/13554794.2011.654211
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia-like psychosis associated with right lacunar thalamic infarct

Abstract: Thalamic dysfunction has been associated with schizophrenia and other psychotic disorders. We describe an adult patient with a lacunar infarct in the posterior region of the right thalamus exhibiting a paranoid schizophrenia-like psychosis as the only clinical manifestation. Neuropsychological assessment showed alterations in visuospatial memory and executive functions at follow up. This case highlights the role of information processing by the thalamus in the development of delusions. We suggest that dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 25 publications
1
11
0
1
Order By: Relevance
“…Recent studies support this mechanism: the neurotoxic effects of ketamine in rodents appears to occur through action in the thalamus, as opposed to direct effects on cortical brain regions (Sharp et al 2001); reductions in thalamic blood flow have been shown to occur following administration of the serotonergic hallucinogen psilocybin (Carhart-Harris et al 2012); and several case reports of patients with thalamic infarct describe the sudden onset of a schizophrenia-like psychosis (Arikan et al 2009;Mittal and Khan. 2010;Crail-Melendez et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies support this mechanism: the neurotoxic effects of ketamine in rodents appears to occur through action in the thalamus, as opposed to direct effects on cortical brain regions (Sharp et al 2001); reductions in thalamic blood flow have been shown to occur following administration of the serotonergic hallucinogen psilocybin (Carhart-Harris et al 2012); and several case reports of patients with thalamic infarct describe the sudden onset of a schizophrenia-like psychosis (Arikan et al 2009;Mittal and Khan. 2010;Crail-Melendez et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The thalamus plays a critical role in the coordination of information as it passes between several brain regions . A disruption of that information flow may give rise to some of the cardinal symptoms of SCZ and BD, as suggested by previous studies showing: (1) altered thalamic volumes in BD and SCZ patients; (2) reduced neuronal density in post‐mortem thalamic samples of SCZ patients; (3) altered thalamic glutamate receptor expression and elevated dopamine in thalamic sub‐regions; (4) emergence of SCZ‐like syndromes when illnesses, such as stroke, selectively damage the thalamus while sparing the rest of the brain …”
Section: Discussionmentioning
confidence: 99%
“…53 Schizophrenics are thought to be overwhelmed with information and stimuli due to deficient thalamoreticular circuits that may lead to delusion and hallucination. 13,54 Thus, anatomical and functional variations of the thalamus are likely reflected in differences in sensory gating and filtering of information and stimuli that may or may not lead to schizophrenia-like perceptual experiences. Collectively, fast sleep spindle density seems to be a promising and sensitive spectrum marker for schizophrenia.…”
Section: Discussionmentioning
confidence: 99%